2003
DOI: 10.1073/pnas.2135217100
|View full text |Cite
|
Sign up to set email alerts
|

PPARγ coactivator 1β/ERR ligand 1 is an ERR protein ligand, whose expression induces a high-energy expenditure and antagonizes obesity

Abstract: A well balanced body energy budget controlled by limitation of calorie uptake and͞or increment of energy expenditure, which is typically achieved by proper physical exercise, is most effective against obesity and diabetes mellitus. Recently, peroxisome proliferator-activated receptor (PPAR) ␥, a member of the nuclear receptor, and its cofactors have been shown to be involved in lipid metabolism and in the control of energy expenditure. Here we show that PPAR␥ coactivator 1 (PGC-1) ␤ functions as ERRL1 (for ERR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
290
1
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 330 publications
(308 citation statements)
references
References 26 publications
14
290
1
2
Order By: Relevance
“…62,63 Esrraand Esrrg-mediated regulation of target gene occurs in part through the direct activation of Ppara gene transcription, using Ppargc 1a or 1b (Pgc1a and Pgc1b) as coactivators. [64][65][66][67] In this study, fenofibrate did not cause significant changes in the hepatic expression of the Ppara gene (1.39-fold reduction) as assessed by the microarray analysis and confirmed by northern blotting. However, the protein levels of Ppara were increased in the liver of the fenofibrate-treated mice.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…62,63 Esrraand Esrrg-mediated regulation of target gene occurs in part through the direct activation of Ppara gene transcription, using Ppargc 1a or 1b (Pgc1a and Pgc1b) as coactivators. [64][65][66][67] In this study, fenofibrate did not cause significant changes in the hepatic expression of the Ppara gene (1.39-fold reduction) as assessed by the microarray analysis and confirmed by northern blotting. However, the protein levels of Ppara were increased in the liver of the fenofibrate-treated mice.…”
Section: Discussionsupporting
confidence: 53%
“…In addition, the fenofibrate treatment caused 1.5-and 2.03-fold reduction in the expression of Pgc1a and Pgc1b genes, respectively, which are key coactivators of genes involved in mitochondrial oxidative metabolism as well as other cellular energy metabolic pathways. 67,[70][71][72][73][74] It is possible that Esrrg may bind to the promoters of fenofibrateinducible genes and in synergy with Ppara may activate their transcription. It has been reported that in mouse fibroblast double-deficient for Ppara and Esrra, the addition of Esrra or Ppara alone fails to activate several Ppara target genes, and supports the concept of synergy between these two transcription factors in the activation of Ppara-inducible genes.…”
Section: Discussionmentioning
confidence: 99%
“…ERRα is involved in many aspects of lipid metabolism, likely by mediating actions of PGC-1α and -β (Kamei et al 2003;Schreiber et al 2003;Schreiber et al 2004;RodriguezCalvo et al 2006;Sonoda et al 2007). In the mouse intestine, ERRα controls the ApoA-IV promoter and loss results in reduced uptake of lipids (Luo et al 2003;Carrier et al 2004).…”
Section: Errαmentioning
confidence: 99%
“…128 PPARG coactivator 1B (PGC1B) is a recently discovered homologue of PGC1A, which, like PGC1A, in experimental animals induces expression of genes involved in oxidative phosphorylation. 129,130 PGC1B expression in human adipose tissue relative to obesity has to our knowledge not been investigated. One coding PGC1B SNP, Ala203Pro, has in a Danish population been reported to protect against obesity.…”
Section: Pathways Controlling Lipid Storage In Adipocytesmentioning
confidence: 99%